2005
DOI: 10.1016/j.margeo.2004.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-industrial environmental changes as revealed by the biogeochemical sedimentary record of Drammensfjord, Norway

Abstract: The biogeochemical sedimentary record of the anoxic Drammensf jord, Norway, was investigated on a decadal to centennial time scale over the last millennium, in order to reconstruct the pre-industrial f jord environment and ecosystem and humaninduced environmental changes. The sediments were dated by a combination of 14 C and 210 Pb analysis and varve counting. Analysis of the bulk sedimentary parameters and of the biomarker distribution revealed that the sedimentary organic matter of the f jord is primarily of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 92 publications
1
25
0
Order By: Relevance
“…These changes correspond to a 20-30% reduction in upwelling and a 1.5-3 • C increase in temperature and suggest climatic influences on productivity (Stott et al, 2000). In deeper parts of Drammensfjord (∼110 m), pyrite-containing laminations indicate that hypoxic conditions have persisted throughout the last 1000 yrs (Alve, 1990(Alve, , 1991Smittenberg et al, 2005). Laminations are developed in other Norwegian fjords, for example, at 29-m depth in the Kyllaren Fjord (Smittenberg et al, 2004).…”
Section: Sediment Laminations and Trace Fossilsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes correspond to a 20-30% reduction in upwelling and a 1.5-3 • C increase in temperature and suggest climatic influences on productivity (Stott et al, 2000). In deeper parts of Drammensfjord (∼110 m), pyrite-containing laminations indicate that hypoxic conditions have persisted throughout the last 1000 yrs (Alve, 1990(Alve, , 1991Smittenberg et al, 2005). Laminations are developed in other Norwegian fjords, for example, at 29-m depth in the Kyllaren Fjord (Smittenberg et al, 2004).…”
Section: Sediment Laminations and Trace Fossilsmentioning
confidence: 99%
“…Lipid biomarkers (sterols, fatty acids, fatty alcohols) preserved in sediments are powerful tools for tracing environmental changes (Ficken and Farrimond, 1995;Canuel, 2000, 2002;Smittenberg et al, 2004Smittenberg et al, , 2005. Marine organisms, including bacteria, diatoms and dinoflagellates, produce characteristic lipid biomarkers that track changes in plankton communities in response to eutrophication.…”
Section: Biochemical Indicators: Pigments and Lipid Biomarkersmentioning
confidence: 99%
“…Mollenhauer et al 2006). The influx of anthropogenic carbon, mostly from fossil fuel burning and spills have been extensively investigated (Reddy et al 2002a,b;Tanner et al 2004;Slater et al 2005Slater et al , 2006Smittenberg et al 2005;White et al 2005;Wakeham et al 2006). Interestingly, not all suspected pollution indicators are necessarily man-made.…”
Section: Biogeochemistry and Microscale Amsmentioning
confidence: 99%
“…Thus far, only three studies reported the carbon isotopic composition of branched GDGTs (Pancost and Sinninghe Damsté, 2003;Smittenberg et al, 2005;Oppermann et al, 2010). The foremost reason for such few studies is that GDGT lipids themselves are not GC-amenable, and carbon isotopic determinations typically require either offline isolation (using, for example, preparatory liquid chromatography) of GDGTs or the chemical cleavage of the ether bonds, thereby releasing the GC-amenable octacosane components.…”
mentioning
confidence: 99%
“…The glycerol units, however, comprise fewer than 10% of the carbon atoms of the whole tetraether. Using the first approach, Smittenberg et al (2005) reported δ 13 C values of −28.4‰ and −28.6‰ in sediment samples from Drammensfjord, Norway. These branched GDGT are most likely derived from forested soils in the catchment of the Drammen river and soils directly surrounding the fjord (Huguet et al, 2007).…”
mentioning
confidence: 99%